O lugar das instituições custodiadoras de documentos arquivísticos públicos municipais mineiros no Programa “ICMS Patrimônio Cultural” − Lei Robin Hood - Edinaldo Medina Batista (2023)
This dissertation deals with the subject of "ICMS Cultural Heritage - Robin Hood Law". The state of Minas Gerais (Brazil) has established criteria for the monthly distribution of the financial amounts related to the transfer of the Tax on the Circulation of Goods and Services (ICMS) to the municipalities of Minas Gerais (especially the poorest ones). One of the pioneering aspects of the Robin Hood Law is the inclusion of the "cultural heritage" criterion within the scope of the transfer of ICMS funds to the municipalities. The aim is to answer the following research problem: “Is it possible to prove a connection between the institutions that hold public archival documents in Minas Gerais and the score given by the ICMS Cultural Heritage (Robin Hood Law) to municipalities in the state of Minas Gerais?”. The general objective was to identify the institutions that hold municipal public archival documents in the state of Minas Gerais that contribute, directly or indirectly, to the municipality's score in the ICMS Cultural Heritage - Robin Hood Law. It was based on the collection of documentary sources and legislative and bibliographical references, as well as on comparing data on municipalities that declare that they have archives on the website of the Brazilian Institute of Geography and Statistics (IBGE), from the National Register of Archives Custodians (CODEARQ), the Brazilian Directory of Archives (DIBRARQ), the website, table and spreadsheet data of the Minas Gerais State Institute of Historical and Artistic Heritage (IEPHA-MG), the Integrated Access System of the Minas Gerais Public Archives (SIAAPM) and the website of the "Belo Horizonte Metropolitan Region Archives Observatory Project (POARMBH)". It was found that 18 custodian institutions contributed directly to the score of their respective municipalities: Airuoca, Alfenas, Araguari, Araxá, Barbacena, Bicas, Catas Altas da Noruega, Chiador, Conselheiro Lafaiete, Coronel Fabriciano, Guarará, Itajubá, Juiz de Fora, Mato Verde, Muriaé, Ponte Nova, Teófilo Otoni and Uberaba, both through the listing or inventory of their documents (movable property) and through the building or place that holds these documents (immovable property). It was concluded that the greater the presence of a custodian institution in a municipality or a region, the greater the chances of its cultural assets being transferred to the executive branch and, above all, to the municipal legislature, generating revenue and transfers to the respective municipalities in terms of the ICMS Cultural Heritage − Robin Hood Law.